ABOUT UKRAINE AGAIN; THE MINSK II AGREEMENT – BETWEEN HOPE AND NEW CHALLENGES - Paraschiva Bădescu (Romanian Journal of Historical Studies)
The military conflict in East-Ukraine threatens security not only in this area of Europe, but in the world as a whole, involving the Russian Federation, USA, and many countries of Europe, NATO and the European Union. Unsuccessful attempts to put an end to the conflict led to the intervention of the leaders of Germany and France, who negotiated along with V. Putin and V. Poroshenko the Minsk II Agreement, a very complex arrangement, including not only the cease fire, but also the withdrawal of heavy weaponry from the area under the OSCE monitoring and internal Ukrainian constitutional changes meaning also a wide statute of autonomy for the regions Donetsk and Lugansk. Will this agreement resist? Will it be implemented? For the EU, which has enough problems of its own, including discontent with regard to sanctions applied to Russian Federation, the continuation of the conflict is unacceptable. USA would think to give military assistance to Ukraine, in terms of new weapons and training for its military. European States are not favorable to such an evolution. Many people ask themselves if this conflict is not the expression of a strategy of the Russian Federation to rebuild its area of influence to what USSR had before 1989. This would open a kind of a new cold war, with unknown consequences. This study is not proposing to give answers to such questions; it is rather opening an area of reflection for all those interested